Pengaruh Belanja Modal Dana Perimbangan dan Pendapatan Asli Daerah Terhadap Kinerja Keuangan Daerah Kabupaten/Kota di Provinsi Sumatera Utara Tahun 2019-2022 - Juwita, Anggi; Hasbi, Khairita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This research aims to determine the influence of capital expenditure, balancing funds and local original income on regional financial performance. The population in this research is 33 Regencies/Cities in North Sumatra Province which have data on the realization of the Revenue and Expenditure Budget (APBD) for the 2019-2022 period. The amount of expenditure for each region varies according to the size of region and regoinal needs. The data is processed using panel data regression. The result of the research show that capital expenditure has a positive and significant effect on regional financial performance, balancing funds have a negative and significant effect on regional financial performance,, and local original income has a positive and significant effect on regional financial performance in Sumatera Utara Province.